PENERAPAN TERAPI MINDFULNESS DALAM MENGATASI KECEMASAN PADA PASIEN HEMODIALISA DI PUSKESMAS HAJIMENA TAHUN 2023 - Setia Rana Ulfa; Giri Susanto (Yayasan Nusantara Hasana Berdikari, 2023)
GGK patients undergo hemodialysis therapy 2-3 times each week, and spending several hours will make them experience tension, anxiety, and depression that varies from individual to individual, negatively affecting their quality of life and health—a form of non-pharmacological intervention that can reduce anxiety non-pharmacologically through mindfulness practice. This nursing care aims to apply mindfulness therapy in overcoming anxiety in hemodialysis patients at the Hajimena Health Center in 2023. The design of this scientific paper uses a descriptive design. The method of collecting data in this scientific paper uses observation and application of mindfulness therapy in overcoming anxiety in hemodialysis patients at the Hajimena Health Center that has been selected. The results of the implementation carried out in the management of anxiety with mindfulness were carried out for three consecutive days. The evaluation results in case I, Mrs. L, and case II Mrs. S found that on July 10, Mrs. L scored an anxiety level of 15 (severe anxiety category), Mrs. S scored 16 (severe anxiety category); on July 11, 2023, Mrs. L score 11 (moderate anxiety category) Mrs. S score 12 (moderate anxiety category) and on July 12, 2023, Mrs. L with a score of 8 (mild anxiety category) on Mrs. S score 9 (mild anxiety category). From the above results, it can be concluded that mindfulness therapy is very effective in reducing the level of anxiety experienced by hemodialysis patients. It is hoped that GGK patients can do mindfulness regularly to reduce the anxiety experienced.